Reflexe paduanischer Universitätsphilosophie bei Durich Chiampell - Caduff, Gian Andrea (Zwingliana, 2025)
At the beginning of a treatise written for the Graubünden Synod of 1577 to falsify the derivation of sin from a Scotist understanding of God’s omnipotence, as it had become known in the Lower Engadine through two Italian Capuchins who had converted to the Reformation, but continued the way of Franciscan thinking, the Engadine reformer Durich Chiampell polemizes against old and new Epicureans. While the latter were characterized by the reception of the original Epicureanism on the basis of the Lucretius manuscript discovered by Poggio Bracciolini during the Council of Constance, the term "old Epicureans" refers back to an expansion of meaning that the term had experienced through its transfer to radical Aristotelianism, which had been challenging official orthodoxy since the 13th century. In nearby Padua it persisted until the 17th century and from there spread to Graubünden in a variety of forms.